Chronic Ventricular Assist Device Support in Adult Congenital Heart Disease Patients: A Children's Hospital Perspective. Issue 12 (26th October 2021) - Perry, Tanya; Lorts, Angela; Morales, David L. S.; Fields, Katrina; Fahnhorst, Sarah E.; Brandewie, Katie; Lubert, Adam; Villa, Chet R.
Abstract : With improvement in early surgical outcomes in patients with complex congenital heart disease, most patients are now expected to survive to adulthood. As adult congenital heart disease (ACHD) patients age, they are at risk of heart failure, which has become the leading cause of mortality in ACHD. Some who develop advanced heart failure may not be candidates for transplant, and chronic ventricular assist device (VAD) therapy may be the only means of survival. There is limited experience with chronic VAD therapy in ACHD patients, and the outcomes are not well delineated. We describe our center's experience with chronic VAD therapy in ACHD patients receiving care exclusively within our children's hospital.